2022
DOI: 10.1039/d2ra00136e
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of new Cdc2-like kinase 4 (CLK4) inhibitors via pharmacophore exploration combined with flexible docking-based ligand/receptor contact fingerprints and machine learning

Abstract: Ligand-based pharmacophores, ligand–receptor contact fingerprints, physicochemical descriptors and machine learning were combined to probe binding of potent CLK4 antagonists. GFA-SVR gave the best model. Virtual screening identified 3 nanomolar hits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…It is noteworthy that certain CLKs inhibitors were recognized as ideal lead compounds for structural optimization to obtain more specific CLKs inhibitors. Moreover, a genetic function algorithm support vector regression (GFA-SVR) 171 and ligand- or structure-based drug optimization 172 , 173 provided predictive models and effective methods for screening and optimizing of the potential of CLKs inhibitors. Nonetheless, research on CLKs-based therapy is still in the initial stage; the cognition and development of CLKs inhibitors will undoubtedly progress upon more in-depth investigation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…It is noteworthy that certain CLKs inhibitors were recognized as ideal lead compounds for structural optimization to obtain more specific CLKs inhibitors. Moreover, a genetic function algorithm support vector regression (GFA-SVR) 171 and ligand- or structure-based drug optimization 172 , 173 provided predictive models and effective methods for screening and optimizing of the potential of CLKs inhibitors. Nonetheless, research on CLKs-based therapy is still in the initial stage; the cognition and development of CLKs inhibitors will undoubtedly progress upon more in-depth investigation.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…We have imported the experimentally-determined 3D structures of 5-HT2C and CLK4-KD proteins from the Protein Data Bank (PDB) [53]. The structure of 5-HT2C (PDB: 6BQH) is in complex with ritanserin in the binding site, while CLK4-KD (PDB: 6FYV) is in complex with 5-[(3-chlorophenyl)amino]benzo[c]- [2,6]naphthyridine-8-carboxylic acid (3NG) compound in the binding site [27,42]. The grid parameters were created to only include the proteins binding sites; they are shown in Table I.…”
Section: Molecular Docking Approachmentioning
confidence: 99%
“…One of these CLKs isoforms CLK4-KD is involved in the phosphorylation of serine, arginine, threonine and tyrosine residues and is crucial in the control of fundamental cellular activities. This kinase may be a target for several diseases, including cancer, Duchenne muscular dystrophy, inflammatory and viral diseases, or neurodegenerative diseases [2,16,38,40,51]. Despite these considerations, just a few numbers of computer-aided molecular design and discovery studies focused on CLK4 and 5-HT2C receptors modulators were reported.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Clk4 is involved in alternative splicing and RNA processing in Duchenne muscular dystrophy, Alzheimer's disease, HIV-1, influenza virus. [27] Furthermore, its expression is correlated with poor patient survival in triple-negative breast cancer (TNBC) patients, also highly overexpressed in many types of cancer including lung, larynx, colon, rectum, melanomas, glioblastomas, and sarcomas. [26,28,29] Despite the importance of Clk4 in neurodegenerative diseases and cancer, it seems that no selective inhibitors targeting Clk4 have been reported.…”
Section: Introductionmentioning
confidence: 99%